The Uncertain Future of Shorebirds on the Delaware Bay (New Jersey Department of Environmental Protection (NJDEP), Division of Fish and Wildlife, Endangered Species Program, 2003)
This presentation covers the results of four investigations authored by prominent shorebird scientists from around the world. These studies cover five different species that migrate from Arctic breeding areas to South American wintering areas. On their northbound return the birds stopover on the Delaware Bay. This presentation concentrates on the red knot, as it is the most dependent on the Delaware Bay. It shows that there has been a significant decline in the ability of shorebirds to gain weight, a decline in survival rates, and a drastic decline in the wintering population.